Studi Tentang Stres Kerja yang Berdampak Pada Kinerja Karyawan - Wina Oktafiana Dafinci; Meiliani Meiliani; Paulus Suluk Kananlua (The Manager Review, 2020)
The purposes of the study are to explore the work stress and job performance of bank’s employees, and to identify factors that influence work stress that have an impact on bank’s employees. The employees of the back office section at Head Office, Bank of Bengkulu are chosen as the respondents and participants for the questionnaire and interview surveys. An electronic questionnaire is distributed to the respondents and an interview protocol is used to interview participants. The surveys’ results reveal that the perceptions of the employees on the work stress of the  intrinsic factors at work have less impact, the relationship at work and the  organizational climate are very conducive, and the organizational role is positive. In the meantime, the job performance has a high rating. Four factors that influence the work stress are the same as the dimensions on the stress concept with more focus on certain items. The relationship at work strengthens on the intensive supports from coworkers and the active interactions with co-workers. The organizational climate includes the task demands in a timely manner, the independent in determining work completion procedures, the recognition or appreciation, and support for creativity. The intrinsic factors at work consist of the excessive workloads, the monotonous work, and the noise level. The organisational roles emphasise on the conflicting tasks with family and excessive roles (doing different tasks). One new factor emerged is the career growth consisting of the opportunity of self-development and the chance for promotion. The results imply that the work stress and the job performance supported the concept of both variables and the concept of work stress existed in the workplace. The employees’ welfares, the fair performance appraisal, and employee engagement should be promoted in order to reduce the work stress and to increase the job performance.